Analisa Algoritma C.45 Terhadap penentuan Rekomendasi Penerima Beasiswa SMP Swasta Methodist-8 Medan - Sipayung, Sardo Pardingotan; Sihaloho, Tulus Pramita; Purba, Ade; Tarigan, Jenheri Rejeki (LOFIAN: Jurnal Teknologi Informasi dan Komunikasi, 2023)
Scholarships are financial assistance with the intention to be used as a means of continuing education that is taken and is usually given by foundations, companies and government agencies. Scholarships in the form of funds used to help underprivileged students in continuing their task of completing education. Therefore the scholarship must be on target to the recipient who is truly feasible and deserves to get it. The number of prospective recipients makes the selection process take a long time. In this case the use of data mining methods can be used as a solution to facilitate the selection process. The C4.5 algorithm is an algorithm that will be used in this study. The data used are the names of students, classes, parents' income, dependents of parents, and the average report card value. Data mining processing on a training data will produce a decision tree. The evaluation method carried out in this test was obtained by the accuracy value of 93.33 %, this could be proof that the C4.5 algorithm was accurate enough to provide scholarship recommendations.